A Reflection and Relevance of Lectures and Organizational Performance in The Pandemic Time Covid-19 - Faisal Rahman Dongoran; Indra Maipita; Abdul Hamid K (Journal of Educational Science and Technology (EST), 2021)
This study aims to determine the effect of lecturer competence and commitment on their teaching performance during the Covid-19 pandemic which was remotely (online) carried out through the e-learning website. The respondents were 80 permanent lecturers of the faculty of teacher training and education. A quantitative approach with ex post facto study design and path analysis with SPSS v.21 was used. The results showed that the competence variable had a higher influence of 14.5% while commitment was 7.8%. Therefore, 30.9% determined their teaching performance during the Covid-19 pandemic from the contribution of competence and commitment, while 69.1% was from other variables outside the study.